Entrepreneurship in a Unionised Economy - Mikko Leppämäki; Vesa Kanniainen (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper shows that labor market institutions are important for the formation of new enterprises. The effects of labor market institutions on entrepreneurship, wage determination, and firm size are analysed analytically and illustrated numerically. The main result is that an increase in union power reduces the equilibrium rate of entrepreneurship and reduces the average size of enterprises.
Keywords: J23; J24; J51; M13; 330; Entrepreneurship; labor market institutions; occupational choice; unions